Puparial Cases as Toxicological Indicators: Bioaccumulation of Cadmium and Thallium in the Forensically Important Blowfly Lucilia sericata - Malejko, Julita; Deoniziak, Krzysztof; Tomczuk, Marlena; Długokencka, Joanna; Godlewska-Żyłkiewicz, Beata (Frontiers in Chemistry, 2020)
In this study we present entomotoxicological data on the accumulation of cadmium and thallium in a forensically important blowfly, Lucilia sericata, and evaluate the reliability and utility of such information as toxicological evidence for poisoning as a cause of death. We observed that Cd and Tl content in different growing stages of Lucilia sericata (larvae, puparial cases and adults) was increasing with increasing metal concentration in the feeding substrate, namely metal-enriched liver. However, patterns of accumulation differed between the two metals investigated, showing a linear relationship for Cd and a saturable pattern for Tl. For cadmium, the highest bioaccumulation factor (BAF) was found in the larval stage (in the range of 0.20–0.25), while for thallium, puparial cases accumulated more metal than the other stages tested (BAF in the range of 0.24–0.42). Thallium was also observed to have a negative effect on larval growth, resulting in lower weight and smaller puparial size. With this study, we update the information on the bioaccumulation of cadmium in forensically important blowflies and provide the first report on the bioaccumulation of thallium as well as its developmental impact in blowflies. Specifically, our results suggest that analysis of puparial cases could yield useful information for entomotoxicological investigations. Due to limited amount of samples, The content of Cd and Tl in larvae, puparial cases, and adults of Lucilia sericata was determined by inductively coupled plasma mass spectrometry (ICP-MS). The validation parameters of the method such as sensitivity, detection limits, quantification limits, precision, and accuracy were evaluated. The method detection limit (MDL) for all types of samples was in the range of 1.6–3.4 ng g-1 for Cd and 0.034–0.15 ng g-1 for Tl, and the accuracy of the method was confirmed by a high recovery of metals from certified reference materials (91.3% for Cd and 94.3% for Tl).